2013
DOI: 10.4187/respcare.02455
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory System Deposition with a Novel Aerosol Delivery System in Spontaneously Breathing Healthy Adults

Abstract: BACKGROUND: Intravenous magnesium sulfate (MgSO 4 ) in children and adults with refractory acute asthma is effective, but therapy may be limited by systemic hypotension that might be avoided with the aerosol route. Inhaled MgSO 4 has a relatively high dose (volume) requirement. This, plus the use of inefficient delivery systems, may explain the lack of efficacy of inhaled MgSO 4 in some studies. An in vitro study suggested that the AeroNeb Go with the Idehaler Pocket and a face mask would deliver 16 mg/min of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This high-efficiency delivery system has been shown to deliver 20% of the medication dose to the lungs compared with 4% delivered via conventional nebulizers (eAppendix 5 in Supplement 5). 25,26 Emergency physicians used their clinical judgment to determine the need for additional asthma therapies and made disposition determinations as per usual practice. Discharged children received prescriptions for inhaled albuterol, oral corticosteroid, and inhaled corticosteroid.…”
Section: Methodsmentioning
confidence: 99%
“…This high-efficiency delivery system has been shown to deliver 20% of the medication dose to the lungs compared with 4% delivered via conventional nebulizers (eAppendix 5 in Supplement 5). 25,26 Emergency physicians used their clinical judgment to determine the need for additional asthma therapies and made disposition determinations as per usual practice. Discharged children received prescriptions for inhaled albuterol, oral corticosteroid, and inhaled corticosteroid.…”
Section: Methodsmentioning
confidence: 99%
“…Children enrolled in the RCT who continued to experience moderate to severe respiratory distress, 19 , 20 defined by a PRAM score of 5 points or higher 19 ( Table 1 ) 21 after 1 hour of standardized initial treatment with systemic corticosteroids and 3 treatments with inhaled albuterol and ipratropium bromide, were randomly assigned to receive three 20-minute treatments of nebulized albuterol (5 mg) plus either nebulized magnesium sulfate (600 mg) or 5.5% saline placebo via a pretested, high-efficiency Aeroneb Go nebulizer (Philips). 22 , 23 After completion of this therapy (60 minutes after randomization), the ED physicians prescribed additional treatments such as IV magnesium sulfate as needed and decided whether to hospitalize patients according to their clinical judgement.…”
Section: Methodsmentioning
confidence: 99%
“…To ensure adequate delivery of the experimental treatment into the lungs, we have pre-tested the Aeroneb™ Go Micropump Nebulizer along with the Idehaler™ Pocket system without valves that connects with a facemask in vitro and in vivo. We found that this device deposited 20 % of the charge dose compared to 4 % by conventional nebulizers, while also maintaining acceptable osmolarity and safety [ 74 ]. This device has been distributed to all participating sites, related training provided, and Health Canada approval obtained.…”
Section: Methodsmentioning
confidence: 99%